2023
DOI: 10.3390/molecules28145608
|View full text |Cite
|
Sign up to set email alerts
|

Using Potassium Bicarbonate to Improve the Water-Holding Capacity, Gel and Rheology Characteristics of Reduced-Phosphate Silver Carp Batters

Abstract: To study the use of partial or total potassium bicarbonate (PBC) to replace sodium tripolyphosphate (STPP) on reduced-phosphate silver carp batters, all the batters were composed of silver carp surimi, pork back fat, ice water, spices, sugar, and sodium chloride. Therein, the sample of T1 contained 4 g/kg STPP; T2 contained 1 g/kg PBC, 3 g/kg STPP; T3 contained 2 g/kg PBC, 2 g/kg STPP; T4 contained 3 g/kg PBC, 1 g/kg STPP; T5 contained 4 g/kg PBC, and they were all produced using a bowl chopper. The changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…In this study, water was lost during cold storage (Figure 1), thus, the whiteness was lowered with the increase in storage time. In addition, due to the samples with potassium bicarbonate having a darker color and increasing pH (Figure 2) lowering the oxidation rate of myoglobin to metmyoglobin [7], the changes in whiteness between the samples of the 1st and 4th days were not significantly different (p > 0.05). This result indicated that the color of the samples with potassium bicarbonate was more stable than that of the samples without potassium bicarbonate.…”
Section: Whitenessmentioning
confidence: 95%
See 4 more Smart Citations
“…In this study, water was lost during cold storage (Figure 1), thus, the whiteness was lowered with the increase in storage time. In addition, due to the samples with potassium bicarbonate having a darker color and increasing pH (Figure 2) lowering the oxidation rate of myoglobin to metmyoglobin [7], the changes in whiteness between the samples of the 1st and 4th days were not significantly different (p > 0.05). This result indicated that the color of the samples with potassium bicarbonate was more stable than that of the samples without potassium bicarbonate.…”
Section: Whitenessmentioning
confidence: 95%
“…As a result, the sample with potassium bicarbonate had a better water-and fat-holding capacity and lower storage loss [10]. Our previous study found that the processing characteristics of silver carp surimi batter are improved when potassium bicarbonate is used to replace sodium tripolyphosphate [7]. Hence, the addition of potassium bicarbonate increased the stability of water in the cooked silver carp surimi batter during cold storage.…”
Section: Storage Lossmentioning
confidence: 96%
See 3 more Smart Citations